The Effect of An Online Lesson on the Calculation Competence of Medication and Intravenous Fluids in Nursing Students - Thawitsri, Nuanla-or (Journal of The Royal Thai Army Nurses, 2022)
This quasi-experimental research aimed to study the effect of an online Lesson on the calculation competence of medication and intravenous fluids in Nursing Students, a two-group pretest-posttest. The sample was a number of 78 first-year police nursing students enrolled in the Fundamental nursing course in the academic year 2020. The systematic randomizing was divided into an experimental group using the online lesson and a control group using conventional learning. The experiments were conducted over four weeks, and data were collected using: 1) Online Lesson, 2) The knowledge and skill test on the calculation of drugs and intravenous fluids, and 3) The online lesson satisfaction assessment. The data were analyzed by 1) Comparing the average scores of knowledge and skills in the calculation of drugs and intravenous fluids of the students in the experimental group by using a statistical method, paired t-test, 2) Comparing the average scores of knowledge and skills in the calculation of drugs and intravenous fluids between the experimental group with the control group by using a statistical method, independent t-test, and 3) Analyze students’ learning satisfaction toward using the online lesson by using the statistical mean and standard deviation. The results showed that the average scores after learning of the experimental group and the control group were higher than before learning those, and comparison between the experimental group and the control group, the results showed that the average scores of the experimental group were higher than the control group, significant at the .01 level (p<.05)